PENDAFTARAN PEMINDAHAN HAK ATAS TANAH OLEH KEPALA KANTOR PERTANAHAN DALAM “KEDAAN TERTENTU” MENURUT HUKUM TANAH NASIONAL - Khadijah; Achmad Faishal; Rahmida Erliyani (Collegium Studiosum Journal, 2023)
Arrangements for the transfer of land rights are regulated in the provisions of Article 37 Paragraph (1) and Paragraph (2) of Government Regulation Number 24 of 1997 concerning Land Registration. In this case the meaning of "Certain Circumstances" according to the concept of Article 37 Paragraph (2) of Government Regulation No. 24 of 1997 concerning Land Registration and the authority of the Head of the Land Office in registering the transfer of land rights even without being proven by the deed of the Land Deed Making Officer (PPAT). This study uses normative legal methods, with the approach of statutory regulations and other library materials. Based on the results of the author's research that "Certain Circumstances" does not have a clear meaning and uniformity, causing multiple interpretations. As for the authority of the head of the office in carrying out land registration according to the provisions of Article 37 Paragraph (2) has discretionary authority in making policies regarding the transfer of land rights that are not proven by a PPAT deed. Thus, it is necessary to synchronize the laws and regulations governing the registration of land rights by the National Land Agency, especially in the registration of land rights based on deeds that are not made by the PPAT. It would be better if the "Certain Circumstances" referred to were detailed in the body/explanation section so as not to cause multiple interpretations which could become an opportunity for abuse of authority.